2013
DOI: 10.3899/jrheum.130293
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Anti-Peptidylarginine Deiminase Type 4 Antibodies in Rheumatoid Arthritis and Unaffected First-degree Relatives in Indigenous North American Populations

Abstract: Objective The objective of this study was to determine whether anti-peptidylarginine deiminase type 4 (PAD4) antibodies were present in first-degree relatives of rheumatoid arthritis (RA) patients in two indigenous North American populations with high prevalence of RA. Methods Participants were recruited from two indigenous populations in Canada and the United States, including RA patients (probands), their unaffected first-degree relatives, and healthy unrelated controls. Sera were tested for the presence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 30 publications
1
18
1
Order By: Relevance
“…However here, we were not able to demonstrate an antibody response to two different citrullinated PPAD peptides in patients destined to develop RA, suggesting that this is not an early feature in ACPA ontogeny. This is reminiscent of observations made with antibodies to human PAD4 which appear to arise following the ACPA response [ 48 50 ]. Importantly, our data suggest that while smoking is associated with both P.gingivalis infection and RA, smoking does not increase the risk of RA through its association with P.gingivalis .…”
Section: Discussionmentioning
confidence: 64%
“…However here, we were not able to demonstrate an antibody response to two different citrullinated PPAD peptides in patients destined to develop RA, suggesting that this is not an early feature in ACPA ontogeny. This is reminiscent of observations made with antibodies to human PAD4 which appear to arise following the ACPA response [ 48 50 ]. Importantly, our data suggest that while smoking is associated with both P.gingivalis infection and RA, smoking does not increase the risk of RA through its association with P.gingivalis .…”
Section: Discussionmentioning
confidence: 64%
“…91 In addition, an analysis of anti-PAD4 antibodies in American Indian patients with RA and their first-degree relatives revealed that, in contrast with anti-CCP antibodies, these RA-associated autoantibodies were virtually undetectable in the first-degree relatives but were common in patients with established RA. 92 Furthermore, the presence of anti-carbamylated antibodies has been detected in serum samples collected before the onset of RA, 93 and emerging data in patients with established RA suggests that neutrophil extracellular trap (NET) formation are a source of citrullinated autoantigens in RA. 94 In addition, although emerging data is available regarding T-cell reactivity to specific citrullinated proteins and other antigens in patients with established RA, 95,96 no studies to date have directly evaluated the antigen specificity of T-cell and/or B-cell subsets during the preclinical stage of RA and compared this with the ACPA responses.…”
Section: Preclinical Studies In Ra and Slementioning
confidence: 99%
“…The titers of anti-PAD4 autoantibodies were previously analyzed cross-sectionally in non-African populations [ 6 , 8 , 9 ], and studies have determined the prevalence of anti-PAD4 antibodies in established RA to be between 35 and 45 % [ 7 , 10 – 12 ]. The prevalence of these antibodies in the prediagnosis and postdiagnosis time periods has been reported to be 18 % and 26 %, respectively, which suggests that the development of these antibodies occurs mainly over time [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, these autoantibodies have been studied in detail in RA patients of European ancestry and in Native Americans with RA [ 8 , 9 ], but not in patients of African-American ethnicity. It remains unknown whether these antibodies are highly prevalent among African Americans, and whether their presence is associated with erosive disease in the same way it is among patients of other ethnicities [ 6 , 9 ]. The strong association of the HLA-DRB1 locus with ACPA-positive RA provides a rationale for examining the anti-PAD4 response in African Americans with RA [ 14 ].…”
Section: Introductionmentioning
confidence: 99%